1997
DOI: 10.1111/j.1442-2042.1997.tb00318.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Adrenal Cavernous Hemangioma

Abstract: Adrenal hemangiomas are rare tumor. Only 29 surgical cases have been reported. Although rare, adrenal hemangiomas should be included in the differential diagnosis of adrenal neoplasms. We report an additional case of adrenal hemangioma that was removed surgically, and the pertinent literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…They become apparent in the sixth to seventh decade of life, with a 2:1 female-to-male ratio (6). Adrenal hormonal dysfunction is usually absent, with only one case reported of adrenocortical hypersecretion (7). Clinically significant bleeding is rare; spontaneous life-threatening hemorrhage has been reported only by Forbes in a recent paper (8).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They become apparent in the sixth to seventh decade of life, with a 2:1 female-to-male ratio (6). Adrenal hormonal dysfunction is usually absent, with only one case reported of adrenocortical hypersecretion (7). Clinically significant bleeding is rare; spontaneous life-threatening hemorrhage has been reported only by Forbes in a recent paper (8).…”
Section: Discussionmentioning
confidence: 95%
“…To the contrary, Yamada et al published a case that showed only a thin rim without centripetal enhancement (12). The most typical, and therefore crucial, CT and MRI features of hemangiomas are calcifications, phleboliths and enhancement of peripheral vascular lakes, corresponding to the pathologic findings (1,6,7,9). Because ultrasonography is helpful for locating the mass but has little ability in displaying calcifications and phleboliths, CT scan or MRI are always necessary to define the nature of the adrenal neoplasms.…”
Section: Discussionmentioning
confidence: 97%
“…Adrenal haemangiomas are rare, benign, non-functional tumours, with only three cases of hormone-secreting adrenal haemangiomas reported to date 24. Affected individuals are usually between 50 and 70 years of age, and there is a strong predilection for females.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal hemangiomas are non-functioning benign, solid tumors and they are most usually cavernous, unilateral and encapsulated. To date, only 3 cases of hormone-secreting cavernous hemangiomas have been reported [1][2][3][4]. These tumors are more frequent in the sixth and seventh decade of life with female-to-male ratio being 2:1 [3].…”
Section: Introductionmentioning
confidence: 99%